Evaluation of antimicrobial activity and phytochemical screening of red Kamboja (Plumeria rubra L.) extracts - Ni Kadek Yunita Sari; Ni Wayan Deswiniyanti; Putu Angga Wiradana (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Natural antimicrobial sources such as red Kamboja (Plumeria rubra L.) flower extract can be utilized to treat infectious disorders caused by Staphylococcus aureus, Escherichia coli, and Candida albicans. This study aims to determine evaluate the effectiveness of methanol and ethanol extracts of P. rubra floral against E. coli, S. aureus, and C. albicans growth, as well as the amount of secondary metabolites in P. rubra extract. The study's findings indicate that the highest DIZ value of P. rubra methanol extract was 7.40 mm, 7.36 mm, and 7.30 mm for S. aureus ATCC25923 at 5%, 10%, and 20%, respectively, while the highest DIZ value for C. albicans ATCC10231 at 10%, 10%, and 20% was 25.08 mm, and 25.04 mm, respectively. The DIZ value of the P. rubra flower ethanol extract against E. coli strain was 5.26 mm at 5%, and 7.30 mm at 20%. Secondary metabolites of saponins, tannins, alkaloids, flavonoids, steroids, and phenols were present in the methanol and ethanol extracts of P. rubra flowers. In summary, our findings highlight the use of P. rubra flower extract as a biological source with antibacterial properties for the control of human infectious illnesses.